How Preseason Hope Impacts Fans’ Attendance Intentions and Psychological Well-Being - Hyun-Woo Lee; Seong-Jin Park; Kun Chang; Jun-Phil Uhm (Journal of Applied Sports Management, 2024)
The authors developed a two-factor preseason hope scale and examined the moderation effects of preseason hope and state hope on the chain of effects from team identification and attendance intention to subjective well-being. A moderated–moderated mediation model was tested (n=224). Consequently, attendance intention mediated the relationship between team identification and well-being. The effect of team identification on attendance intention was stronger for those with lower preseason hope and state hope. The effect of attendance intention on well-being was stronger for those with higher preseason hope. Interaction effects by levels of hope were found among the conditional indirect effects.
Keywords: preseason hope; state hope; team identification; attendance intention; well-being